Pregeo 10: ad un passo dall’automazione completa - Tufillaro, Donato (GEOmedia, 2010)
Pregeo 10: automation of cadastral processes Nowadays, Public Administration's effectiveness is strictly connected to the availability of its services far from the public offices, directly 'in the houses of the end users'. This is true especially considering that, in Italy as other countries, there are plenty of citizens that live phisically isolated from public structures (ie. small islands). This article features the real experience of an end user that, in spite of the distance, managed to to solve a problem of cadastrial updating through the public online services.